ARTIFICIAL INTELLIGENCE CHATBOT APPLICATION FOR IMPROVING TEACHERS’ SPOKEN GRAMMAR IN SPEAKING IN BINA BHAKTI SCHOOL - Barata, Alvin; Yuliana, Yohanes Gatot Sutapa; Regina, Regina (LPPM Universitas PGRI Pontianak, 2025)
The number of grammatical errors often occurred during conversations in English by teachers in school. Those grammatical errors led to several fatal misunderstandings during some visits from foreign institutes and guests. There were 30 teachers consisting of both Primary and Kindergarten school teachers who were participants in English class for teachers. The purpose of this study was to improve the spoken English grammar of Bina Bhakti school teachers by using artificial intelligence-based application called chatbot which assisted participants to improve spoken grammar with Inductive-Deductive method. The research design was Classroom Action Research (CAR), which was done in two cycles with explanations as opening and chatbot as tool to encourage participants’ speaking ability. The findings showed that there was an improvement in spoken English grammar by giving participants feedbacks regarding their English learning progress. The improvement was made by all participants by number of accuracies to 87.60% from 38.75% in term of number of grammatical errors.